Acute Adhesive Small Bowel Obstruction: a Comparative Analysis of Open and Laparoscopic Surgery - Sh. V. Timerbulatov; V. M. Sibaev; V. M. Timerbulatov; M. V. Zabelin; M. V. Timerbulatov; R. B. Sagitov; A. R. Gafarova (Креативная хирургия и онкология)
Background. Acute adhesive small bowel obstruction (AASBO) is a common surgical emergency requiring immediate interventions. AASBO is a usual indication for both small bowel resection and adhesiolysis. Postoperative adhesions cause 60% of small bowel obstructions.Materials and methods. An analysis of treatment outcomes is presented for 197 acute adhesive small bowel obstruction patients; 63 patients had urgent laparotomy, and 134 were scheduled for laparoscopy. The examination included physical, laboratory, radiological methods (abdominal radiography, ultrasound, CT scan), laparoscopy and intra-abdominal pressure monitoring.Results and discussion. Of 134 patients scheduled for laparoscopic adhesiolysis, only 46.2% had laparoscopy completed, and 53.8% required conversion to laparotomy. The main rationale for conversion were massive adhesions, intraoperative haemodynamic instability, a need for intestinal decompression, as well as rare complications. Laparoscopic operations were reported with the lower vs. laparotomy rates of surgical complications (6.4  vs. 12.69%), mortality (6  vs. 6.3%), shorter hospital stays (6.5 vs. 12 days) and operation times (75 vs. 118 min, respectively).Conclusion. Laparoscopic surgery in acute adhesive small bowel obstruction was feasible in 31.47% patients and in 46.2% — after a diagnostic laparoscopy; however, a thorough patients selection for laparoscopic adhesiolysis is necessary. The first estimated should be the patient’s haemodynamic stability, the severities of condition, adhesions and comorbid cardiorespiratory pathology. Grade I—II adhesions are an indication for laparoscopic surgery.